Sepsis - Valeria Tombini; Sonja Lamberti; Maurizio Bottiroli; Daniele Coen (Emergency Care Journal, 2006)
Sepsis is a complex syndrome difficult to define, to diagnose and to treat. The term defines a group of clinical conditions caused by the systemic answer of the organism to an infection that can cause the dysfunction of one or more organs (severe sepsis) and death. Much more often than one can imagine, ED physicians must diagnose and manage patients with more or less severe sepsis. During the last few years, as it happened for myocardial infarction and stroke, it has been acknowledged the importance of an early treatment also for patients with severe sepsis and septic shock. It has been documented that the attainment of precise haemodynamic goals can influence the prognosis positively. In this work describes recent advances about pathogenesis, diagnosis and therapy of the severe sepsis and septic shock. Innovations on acute and subacute therapy proposed by the Surviving Sepsis Campaign’s collaborative guide lines are presented.